Formal Specification of QoS Negotiation in ODP System - Abdessamad Jarrar; Youssef Balouki; Taoufiq Gadi (International Journal of Electrical and Computer Engineering (IJECE), 2017)
The future of Open Distributed Processing systems (ODP) will see an increasing of components number, these components are sharing resources. In general, these resources are offering some kind of services. Due to the huge number of components, it is very difficult to offer the optimum Quality of service (QoS). This encourages us to develop a model for QoS negotiation process to optimize the QoS in an ODP system. In such system, there is a High risk of software or hardware failure. To ensure good performance of a system based on our model, we develop it using a formal method. In our case, we will use Event-B to get in the end of our development a system correct by construction.